Long-term interest rate spillovers from major developed economies to emerging Asia - Ansgar Belke; Irina Dubova; Ulrich Volz (Asian Development Bank Institute (ADBI), 2017)
This paper explores the extent to which changes to long-term interest rates in major developed economies have influenced long-term government bond yields in emerging Asia. To gauge long-term interest spillover effects, the paper uses vector autoregressive variance decompositions with high-frequency data. Our results reveal that sovereign bond yields in emerging Asia responded significantly to changes to the United States and Eurozone bond yields, although the magnitudes were heterogeneous across countries. The magnitude of spillovers varied over time. The pattern of these variations can partially be explained by the implementation of different unconventional monetary policy measures in developed countries.
Keywords: E52; E58; F42; 330; Long-term interest rates; bond yields; monetary policy spillovers; Emerging Asia